Estimating the undegradable intake protein content of two forages by different commercial proteases - Abdelgadir, I.E.O.; Cochran, R.C.; Vanzant, E.S.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We evaluated the potential of several commercially available proteases for use in predicting the undegradable intake protein (UIP) concentrations o f alfalfa and prairie hay. Protease s differed in their estimates o f the rate of forage protein breakdown an d the amounts of different forage protein fractions . At least one protease appeared to yield acceptable predictions of UIP via a short-term, single time-point assay. Assays of this type deserve further consideration for commercial application.
Keywords: Beef; Protein degradability; Proteases; Forages